Climate Changes Affect Human Capital - Germán Caruso; Inés de Marcos; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2023)
Climate change severely impacts critical facets of human capital across the life cycle. This is particularly alarming as both the frequency and intensity of extreme weather shocks continue to increase, and extremes appear to be the main channel of causality. At the same time, human capital has a vital role in driving effective climate change mitigation and adaptation. Here, we provide a framework for analyzing the multiple interlinkages between climate change and human capital and document the existing evidence on the impacts of climate change damages, and the effects of climate change mitigation and adaptation, on human capital across the life cycle. The framework presents two channels through which human capital is affected: direct effects on health, nutrition, and wellbeing, and indirect effects through changes in economic systems, markets, and through damage to infrastructure. These two channels call for different policy interventions, focusing on the different stages of the life cycle. For mitigation and adaptation, we find that while these are overall clearly beneficial, they are also associated with significant human capital costs for specific sectors and groups in society. Ignoring these costs can only lead to worse outcomes, as it can lead to diminishing public support for the required mitigation and adaptation (as has arguably been the case with globalization). Since there is also evidence that high human capital improves adaptation and mitigation, this suggests that adaptation and mitigation that accounts and compensates for these 'sectoral' losses can create a virtuous cycle that leads to positive outcomes for both climatic action and human capital.
Keywords: I14; I15; I24; I25; Q54; 330; climate change; human capital; mitigation; adaptation; health; education; labor